Himalayan voices : an introduction to modern Nepali literature - Hutt, Michael (Michael J.) (Voices from Asia, 1991)
While the natural splendor of Nepal has been celebrated in many books, very little of the substantial body of Nepali literature has appeared in English translation. Himalayan Voices provides admirers of Nepal and lovers of literature with their first glimpse of the vibrant literary scene in Nepal today. An introduction to the two most developed genres of modern Nepali literature-poetry and the short story-this work profiles eleven of Nepal's most distinguished poets and offers translations of more than eighty poems written from 1916 to 1986. Twenty of the most interesting and best-known example.